2011
DOI: 10.1007/s00109-011-0846-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulation of nNOS and iNOS by CB2 receptor in remote delayed neurodegeneration

Abstract: Hemicerebellectomy results in remote delayed degeneration of precerebellar neurons. We have reported that such a lesion induces type 2 cannabinoid receptor (CB(2)) expression in precerebellar neurons and that stimulation of CB(2), but not CB(1), has neuroprotective effects. In this study, we found that in the same model, the CB(2) agonist JWH-015 enhances neuronal nitric oxide synthase (nNOS) expression in axotomized neurons and that CB(2)-mediated neuroprotection is abrogated by pharmacological inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Repeated administration of the CB2 receptor agonist JWH-105 reduces the inflammatory response to MDMA and provides partial protection against 5-hydroxytriptamine neurotoxicity [60]. Stimulation of CB2 signaling elicits a series of molecular and cellular events that attenuates delayed neurodegeneration [34]. Future studies should be performed in order to evaluate the potential role of CB2 receptors in both neurons and microglia in THC-induced neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated administration of the CB2 receptor agonist JWH-105 reduces the inflammatory response to MDMA and provides partial protection against 5-hydroxytriptamine neurotoxicity [60]. Stimulation of CB2 signaling elicits a series of molecular and cellular events that attenuates delayed neurodegeneration [34]. Future studies should be performed in order to evaluate the potential role of CB2 receptors in both neurons and microglia in THC-induced neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking the nNOS gene are significantly more resistant to N-Methyl-D-aspartate- (NMDA) or METH-induced neurotoxicity and 3-nitrotyrosine production than wild-type mice [31], [32]. Notably, nNOS plays also an important role in cannabinoid-induced neurogenesis and neuroprotection through both the CB1 and CB2 receptors [33], [34]. Few studies have reported that Δ9-THC prevents 3,4-methylenedioxymethamphetamine(MDMA) neurotoxicity [35], [36]; yet, no study has thus far investigated the effects of cannabinoids in METH-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A form of RNS, nitric oxide (NO), production is also increased following TBI [2,61-64] and participates in neurodegenerative cascades [2,27,65]. NO can be derived from different NO-synthase among which is endothelial NOS (eNOS) [66].…”
Section: Introductionmentioning
confidence: 99%
“…The ECS is a ubiquitous ligand-directed signalling system, which has been implicated in regulating a wide range of physiological processes and pathologies, including energy homoeostasis, cardiovascular disease, cancer, and neurodegeneration (Di Marzo and Petrocellis, 2006; Mukhopadhyay et al, 2010b; Oddi et al, 2012). Two key lipid-derived molecules that act as endogenous ligands for this system are anandamide (N-arachidonoylethanolamine, AEA) and 2-arachidonoylglycerol (2-AG)—commonly referred to as endocannabinoids.…”
Section: The Ecsmentioning
confidence: 99%
“…In accord with this, inhibition of LPS-induced NO • release in macrophages by WIN 55,212-2 was shown to be mediated through stimulation of CB2R (Ross et al, 2000). Interestingly, independent work by Oddi et al (2012) revealed that daily treatment of rats with the CB2R agonist JWH-015 for one week markedly attenuated hemicerebellectomy induction of iNOS expression and associated oxidative/nitrosative stress, concomitant with improved neurological outcome measures. Intriguingly, Oddi et al (2012) further demonstrated that JWH-015 treatment increased nNOS expression and activity in axotomized neurons, and the observed neuroprotection conveyed by CB2R activity was abrogated in response to pharmacological inhibition of nNOS.…”
Section: Modulation Of Nitrergic Signalling By the Ecsmentioning
confidence: 99%